Endolymphatic Hydrop Phenotype in Familial Norrie Disease Caused by Large Fragment Deletion of NDP - Gong, Yuerong; Liu, Zhang; Zhang, Xiaolin; Shen, Shuang; Xu, Qijun; Zhao, Hongchun; Shang, Jing; Li, Weiguo; Wang, Yanfei; Chen, Jun; Liu, Xiuzhen; Zheng, Qing Yin (Frontiers in Aging Neuroscience, 2022)
Norrie disease (ND; OMIM 310600), a rare X-linked recessive genetic disorder, is characterized by congenital blindness and occasionally, sensorineural hearing loss, and developmental delay. The congenital blindness of ND patients is almost untreatable; thus, hearing is particularly important for them. However, the mechanism of hearing loss of ND patients is unclear, and no good treatment is available except wearing hearing-aid. Therefore, revealing the mechanism of hearing loss in ND patients and exploring effective treatment methods are greatly important. In addition, as a serious monogenic genetic disease, convenient gene identification method is important for ND patients and their family members, as well as prenatal diagnosis and preimplantation genetic diagnosis to block intergenerational transmission of pathogenic genes. In this study, a Norrie family with two male patients was reported. This pedigree was ND caused by large fragment deletion of NDP (norrin cystine knot growth factor NDP) gene. In addition to typical severe ophthalmologic and audiologic defects, the patients showed new pathological features of endolymphatic hydrops (EH), and they also showed acoustic nerves abnormal as described in a very recent report. PCR methods were developed to analyze and diagnose the variation of the family members. This study expands the understanding of the clinical manifestation and pathogenesis of ND and provides a new idea for the treatment of patients in this family and a convenient method for the genetic screen for this ND family.